Online Mental Health Information Behaviours of Emerging Adults: A Web Usability and User Experience Study - Rasmussen Neal, Diane; Hoffman, Cameron (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This research utilizes Web usability and user experience studies to determine how a small sample of university students ages 18-25 look for and access mental health information online, and how they would like to see the presentation of online mental health information improved. Cette recherche se base sur des études sur la convivialité Web et l’expérience de l’utilisateur pour déterminer comment un petit échantillon d’étudiants universitaires de 18 à 25 ans recherchent et utilisent de l’information sur la santé mentale en ligne, et comment ils aimeraient en améliorer la présentation.